A Case Report of Overcoming an Obstructive, Pedunculated Cervical Fibroid at the Time of Uterine Evacuation - Jayesh Tigdi; Cynthia Chan (Case Reports in Obstetrics and Gynecology)
Background. Fibroids, which can impact pregnancies at later gestations, such as obstructing delivery, may also affect the pregnancy termination process. Case. We present the case of a 28-year-old G1 at 18 weeks who consented for a genetic pregnancy termination via dilation and evacuation. During the typical preparatory procedure with laminaria, it was noted that a 5-6cm cervical fibroid prolapsed into the vagina obstructing access to the uterine cavity. Through osmotic dilation followed by cervical Foley catheter ripening, a planned myomectomy was possible with minimal blood loss prior to uterine evacuation. Conclusion. Through appropriate counselling, planning, and effective cervical dilatation, a planned myomectomy for prolapsing fibroids at the time of termination of pregnancy is possible. This can prevent unnecessary hysterotomy and avoid need for subsequent cesarean section.